Perancangan Sistem Smart Village Ecosystem Untuk Pelayanan dan UMKM Desa Menggunakan Metodologi Agile Scrum - Muhammad Rakha Syamputra; Apriade Voutama (TIN: Terapan Informatika Nusantara, 2026)
The main problem in village management today lies not only in limited digitalization but also in the lack of integration of administrative and economic services. Villages play a strategic role in national development, yet most rural areas in Indonesia are constrained by structural barriers, such as unintegrated public administration, low transparency, and minimal digital technology adoption by Micro, Small, and Medium Enterprises (MSMEs). To address this, this research aims to design an integrated multi-platform Smart Village Ecosystem (SVE) prototype to accelerate village bureaucracy while stimulating local MSME market expansion. This software engineering research was conducted at PT Citiasia Internasional using the Agile Scrum methodology through eight iterative Sprints. System development was implemented using the Laravel framework for the Website and Admin Dashboard, Flutter for the Mobile Application, and MySQL as a database. The system's effectiveness was evaluated through Black-Box Testing, assessing the main features with 10 test scenarios. Results showed that all functions operated perfectly without failures, yielding a functionality score of X = 1, indicating maximum success. In conclusion, the SVE prototype successfully integrated bureaucratic services, community platforms, and digital marketplaces responsively, proving the system is ready for direct implementation in partner villages.